The extraordinary adventures of Alfred Kropp - Yancey, Richard (New York : Bloomsbury : Distributed to the trade by Holtzbrinck Publishers, 2005)
Through a series of dangerous and violent misadventures, teenage loser Alfred Kropp rescues King Arthur's legendary sword Excalibur from the forces of evil.
Keywords: Arthur, -- King -- Fiction; Adventure and adventurers -- Fiction; Orphans -- Fiction